2003
DOI: 10.1248/bpb.26.1701
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sesamin on Aortic Oxidative Stress and Endothelial Dysfunction in Deoxycorticosterone Acetate-Salt Hypertensive Rats

Abstract: Sesamin is one of the lignans contained abundantly in sesame oil. Previous studies have indicated that sesamin inhibits lipid metabolism, such as desaturation in polyunsaturated fatty acid biosynthesis 1) and cholesterol absorption. 2) In recent studies, we have demonstrated the antihypertensive effect of sesamin using several types of experimental hypertensive models. [3][4][5] The most efficient antihypertensive activity was observed in the deoxycorticosterone acetate (DOCA)-salt hypertensive rat model. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
73
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 30 publications
3
73
0
2
Order By: Relevance
“…20,21) In addition, the o-dihydroxyphenyl structure (catechol moiety) at the 3 0 -and 4 0 -positions of B ring flavonoids is necessary for high antioxidative activity, such as radical scavenging and the suppression of lipid peroxidation reactions. 15,17,22) Furthermore, it has been suggested that the gallate group plays an important role in modulating the expression of CAMs in endothelial cells. 9) In the present study, we found that sesaminol-6-catechol had a potent suppressive effect of CAM expression, and that sesaminol, with a hydroxyphenyl group, did not exhibit any inhibitory activity on CAM expression (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…20,21) In addition, the o-dihydroxyphenyl structure (catechol moiety) at the 3 0 -and 4 0 -positions of B ring flavonoids is necessary for high antioxidative activity, such as radical scavenging and the suppression of lipid peroxidation reactions. 15,17,22) Furthermore, it has been suggested that the gallate group plays an important role in modulating the expression of CAMs in endothelial cells. 9) In the present study, we found that sesaminol-6-catechol had a potent suppressive effect of CAM expression, and that sesaminol, with a hydroxyphenyl group, did not exhibit any inhibitory activity on CAM expression (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has a growth-retarding effect on some plants, as well as a synergistic effect with pyretherum insecticides (5,6). (ϩ)-Sesamin has been shown to have a wide range of biological effects: protection against ethanol-and carbon tetrachloride-induced liver damage (7,8), improvement of fatty acid metabolism (9)(10)(11), antiinflammatory effects (12), increased vitamin E activities (13,14), inhibition of vascular superoxide production (15,16), and induction of nitric oxide (17). Therefore, it is an extremely interesting natural compound from the viewpoint of health care (18).…”
mentioning
confidence: 99%
“…Several antioxidative substances have been reported to exert a preventive effect against endothelial dysfunction observed in hypertensive patients and experimental animals (16,18,19). Daily feeding of PBE improves the microcirculation and platelet function in patients with coronary artery diseases.…”
Section: Enhancement Of Nos System By Flavangenolmentioning
confidence: 99%